ปัจจัยทำนายการเผชิญความเครียดของผู้ดูแลผู้ได้รับบาดเจ็บไขสันหลัง - เหมือนชู, สุภาพ; กีรติยุตวงศ์, ภาวนา; วชิราวัธน์, วริยา (Journal of Thailand Nursing and Midwifery Council, 2016)
บทคัดย่อ: วัตถุประสงค์ของการวิจัย: ศึกษาปัจจัยทำนายการเผชิญความเครียดของผู้ดูแล ผู้ได้รับบาดเจ็บไขสันหลัง โดยใช้กรอบทฤษฏีการเผชิญความเครียดของลาซารัสและโฟล์คแมน การออกแบบงานวิจัย: การวิจัยเชิงทำนาย การดำเนินการวิจัย: กลุ่มตัวอย่างจำนวน 82 รายเป็นผู้ดูแลหลักในการดูแลผู้ได้รับ บาดเจ็บไขสันหลังที่มารับการรักษาแผนกผู้ป่วยนอก แผนกเวชกรรมฟื้นฟู และแผนกเวชกรรม สังคม โรงพยาบาลประจวบคีรีขันธ์ เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบประเมินการรับรู้สมรรถนะ แห่งตน การรับรู้ภาวะสุขภาพ สัมพันธภาพในครอบครัว การสนับสนุนทางสังคมจากบุคลากร ทางสุขภาพ และการเผชิญความเครียด วิเคราะห์ข้อมูลโดยใช้สถิติถดถอยพหุคูณ ผลการวิจัย: กลุ่มตัวอย่างใช้การเผชิญความเครียดทั้งวิธีมุ่งแก้ปัญหาและการจัดการ กับอารมณ์ โดยใช้วิธีมุ่งแก้ปัญหามากกว่าการจัดการกับอารมณ์ การสนับสนุนทางสังคมจาก บุคลากรทางสุขภาพ สามารถทำนายการเผชิญความเครียดโดยรวมของกลุ่มตัวอย่างได้ ร้อยละ 28 (R2 = .28, p < .001) การสนับสนุนทางสังคมจากบุคลากรทางสุขภาพและ สัมพันธภาพในครอบครัว สามารถร่วมกันทำนายการเผชิญความเครียดแบบมุ่งแก้ปัญหา ของกลุ่มตัวอย่างได้ร้อยละ 42 (R2 = .42, p < .001) การสนับสนุนทางสังคมจากบุคลากรทาง สุขภาพและการรับรู้ภาวะสุขภาพ สามารถร่วมกันทำนายการเผชิญความเครียดแบบการจัดการ กับอารมณ์ของกลุ่มตัวอย่างได้ร้อยละ 18 (R2 = .18. p <.01) ส่วนการรับรู้สมรรถนะแห่งตน ไม่สามารถทำนายการเผชิญความเครียดได้ ข้อเสนอแนะ: พยาบาลและบุคลากรทางสุขภาพควรส่งเสริมการเผชิญความเครียด ของผู้ดูแลผู้ได้ รับบาดเจ็บไขสันหลังโดยการให้ข้อมูลเกี่ยวกับการดูแล และแสวงหาแหล่ง สนับสนุนอย่างเหมาะสม เพื่อให้เกิดความพร้อมในการดูแล พัฒนาระบบการพยาบาลใน การนำครอบครัวเข้ามามีส่วนร่วมในการดูแล รวมทั้งส่งเสริมภาวะสุขภาพของผู้ดูแล เพื่อเพิ่ม ความสามารถในการเผชิญความเครียดของผู้ดูแลผู้ได้รับบาดเจ็บไขสันหลังได้อย่างเหมาะสม Abstract: Objective: To study factors that could predict the stress-coping ability of caregivers of spinal cord injury patients, based on Lazarus & Folkman’s (1984) stress-coping framework. Design: Predictive research. Implementation: This study was conducted on a sample of 82 main caregivers of spinal cord injury patients being treated at the Out-Patient Department, the Rehabilitative Medicine Department and the Social Medical Service Department of Prajuabkhirikhan Hospital. The research instrument was a form used to collect data on (1) a self-efficacy evaluation; (2) health perception; (3) family relationship; (4) social support by healthcare personnel; and (5) stress-coping strategies. The data were analysed using multiple regression statistics. Results: The stress-coping strategies adopted by the majority of the subjects were problem-solving attempts and emotion management, with the former being preferred over the latter. Social support by healthcare personnel was a factor that could predict the overall stress-coping ability in 28% (R2 = .28, p < .001) of the subjects and, when combined with the factor of family relationship, could predict problem-solving as a stress-coping strategy in 42% (R2 = .42, p < .001) of the subjects. In addition, social support by healthcare personnel and health perception could predict emotion management as a stress-coping strategy in 18% (R2 = .18, p < .01) of the subjects. Self-efficacy perception, on the other hand, was incapable of predicting stress-coping ability. Recommendations: It is recommended that nurses and healthcare personnel provide caregivers of spinal cord injury patients with adequate caring information and help them seek a proper source of support. This could enhance the caregivers’ readiness, strengthen the family-engaged caring system and improve the caregivers’ health by equipping them with proper stress-coping strategies.